The German Facebook case: the law and economics of the relationship between competition and data protection law - Wolfgang Kerber; Karsten K. Zolna (European Journal of Law and Economics, 2022)
Can competition law consider effects on privacy, or should privacy concerns of data-collecting behaviour only be dealt with by data protection law? In this paper, we analyse the German Facebook case, in which the requirement of giving consent to the combination of personal data from different sources was prohibited as exploitative abuse by a dominant firm. We show, from an economic perspective, that due to the simultaneous existence of two market failures (market dominance, information and behavioural problems) and complex interaction effects between both market failures and both policies in digital markets, a new, much more complex relationship emerges. Since the traditional approach of a strict separation of both policies is no longer feasible, a more integrative and collaborative policy approach for competition law and data protection law might be necessary. With respect to the substantive issue in the Facebook case, i.e. protecting a minimum standard of choice for consumers regarding their personal data vis-a-vis dominant digital platform firms, the recent decision by the German Federal Court of Justice in this case and the proposed Digital Markets Act have led to new perspectives for dealing with privacy concerns in competition law and new forms of ex-ante regulation.
Keywords: K21; K24; L40; L50; 340; Competition law; Facebook; Digital platforms; Privacy; Data protection law